2010
DOI: 10.1007/s10495-010-0533-5
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo characterisation of a novel c-FLIP-targeted antisense phosphorothioate oligonucleotide

Abstract: Previous studies have suggested that the caspase 8 inhibitor FLIP is a promising anti-cancer therapeutic target. In this study, we characterised a novel FLIP-targeted antisense phosphorothioate oligonucleotide (AS PTO). FLIP AS and control PTOs were assessed in vitro in transient transfection experiments and in vivo using xenograft models in Balb/c nude mice. FLIP expression was assessed by QPCR and Western. Apoptosis induction was determined by flow cytometry and Western. Of 5 sequences generated, one potentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…We have previously shown that RNAi- and antisense-mediated FLIP downregulation induces apoptosis in NSCLC cell lines in vitro and in vivo 7, 23 and that the sensitivity of NSCLC cells to FLIP downregulation is dependent on their elevated expression of procapase-8. 7 Thus, FLIP represents an attractive therapeutic target in this disease.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that RNAi- and antisense-mediated FLIP downregulation induces apoptosis in NSCLC cell lines in vitro and in vivo 7, 23 and that the sensitivity of NSCLC cells to FLIP downregulation is dependent on their elevated expression of procapase-8. 7 Thus, FLIP represents an attractive therapeutic target in this disease.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, an antisense phosphorothioate oligonucleotide (AS PTO) targeting FLIP sensitized several cancer cell lines but not a normal lung cell line to TRAIL-induced apoptosis. This FLIP-targeted AS PTO also efficiently enhanced apoptosis in xenograft models (53). These studies suggest that direct targeting of FLIP may be beneficial as therapy in combination with TRAIL to circumvent and prevent TRAIL resistance.…”
Section: Flipmentioning
confidence: 99%
“…Pretreatment with chemotherapeutic drugs including cisplatin, doxorubicin, or topoisomerase I inhibitors (camptothecin, 9-NC, irinotecan) downregulated c-FLIP variants expression in various tumor cells by inhibiting its transcription and rendering cells sensitive to death receptor-triggered apoptosis (Table 1) [69,143-148]. Successful inhibition of malignant cell growth and apoptosis induction using histone deacetylase inhibitor (HDACi) compounds has highlighted the potential use of these compounds as anticancer agents.…”
Section: Cellular Flice-like Inhibitory Protein (C-flip)mentioning
confidence: 99%
“…Logan et al [143] investigated whether using an antisense oligonucleotide to target c-FLIP was a clinically feasible approach (Table 2). These authors developed a novel c-FLIP-targeted antisense phosphorothioate oligonucleotide (AS PTO) and recently used it in vitro in transient transfection experiments and in vivo using xenograft models in Balb/c nude mice [143]. The AS PTO downregulated c-FLIP and resulted in caspase-8 activation and apoptosis induction in non-small cell lung cancer (NSCLC) cells, but not in normal lung cells.…”
Section: Cellular Flice-like Inhibitory Protein (C-flip)mentioning
confidence: 99%